Практика и перспективы применения процессов обогащения при переработке продукта синтеза кубического нитрида бора - Богатырева, Г.П.; Олейник, Н.А.; Базалий, Г.А.; Гвяздовская, В.Л.; Пюра, Г.Г.; Шамраева, В.С. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The results of the many years of experience and also application perspectives of enrichment processes in resourcesaving technology of the treatment of product cubic carbon nitride synthesis are indicated. The processes and technology of the treatment are based on the results of influence of active physicochemical environment and mechanical destruction on the technological, structureabsorptive and physicochemical properties of the composite technological material and its components.